2012
DOI: 10.1186/1750-1326-7-36
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal expression of murine IL-4 results in exacerbation of amyloid deposition

Abstract: BackgroundPro-inflammatory stimuli, including cytokines like Interleukin-1β, Interleukin-6 and Interferon-γ, in the brain have been proposed to exacerbate existing Alzheimer’s disease (AD) neuropathology by increasing amyloidogenic processing of APP and promoting further Aβ accumulation in AD. On the other hand, anti-inflammatory cytokines have been suggested to be neuroprotective by reducing neuroinflammation and clearing Aβ. To test this hypothesis, we used adeno-associated virus serotype 1 (AAV2/1) to expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
68
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 48 publications
(67 reference statements)
5
68
0
Order By: Relevance
“…There is a large amount of evidence to show that increased proinflammatory cytokines correlates with Aβ production and neurodegeneration. In contrast, there are also a number of studies indicating that proinflammatory cytokines precondition the system for Aβ challenge and protect against neurodegeneration (82)(83)(84)(85). Clearly, inflammation is a major component of the AD brain, and more work will be required in order to elucidate its role in AD pathogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…There is a large amount of evidence to show that increased proinflammatory cytokines correlates with Aβ production and neurodegeneration. In contrast, there are also a number of studies indicating that proinflammatory cytokines precondition the system for Aβ challenge and protect against neurodegeneration (82)(83)(84)(85). Clearly, inflammation is a major component of the AD brain, and more work will be required in order to elucidate its role in AD pathogenesis.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, the relationship of IL-4 to AD pathology is very complex. It has been reported that overexpression of IL-4 in TgCRND8 mice increased Aβ deposition [25]. IL-4 has also been shown to increase the clearance of oligomeric Aβ by microglia in vitro and decrease Aβ deposition in APP/PS1 transgenic mice [26,27].…”
Section: Discussionmentioning
confidence: 97%
“…Though these types of 'conversion studies' are associated with severe inherent limitations, they substantiate the potential diagnostic relevance of neuroinflammatory cytokine alterations in AD [185]. Despite the proposed and increasingly established roles of proinflammatory cytokine alterations in disease pathogenesis in AD, controversial results have also been published demonstrating deleterious effects of anti-inflammatory cytokines and beneficial effects of proinflammatory cytokines in terms of brain Aβ clearance in vivo [186][187][188][189][190]. Of note, generally disappointing results have been obtained from studies aiming at the modification of inflammatory response in AD with nonsteroidal anti-inflammatory drugs (NSAIDs) or elective cyclooxygenase-2 (COX-2) inhibitors at the clinical level [191][192][193][194][195].…”
Section: Neuroinflammation In Alzheimer's Diseasementioning
confidence: 99%